Mass Cytometry Studies of Patients With Autoimmune Endocrine Diseases Reveal Distinct Disease-Specific Alterations in Immune Cell Subsets - Magnusson, Louise; Barcenilla, Hugo; Pihl, Mikael; Bensing, Sophie; Espes, Daniel; Carlsson, Per-Ola; Casas, Rosaura (Frontiers in Immunology, 2020)
Although there is evidence that autoimmune diseases share similar immunogenetic mechanisms, studies comparing peripheral CD45+ cells from patients with autoimmune endocrine diseases in parallel are limited. In this study, we applied high-dimensional single-cell mass cytometry to phenotypically characterize PBMC from patients with new-onset (N-T1D) and long-standing type 1 diabetes, Hashimoto’s thyroiditis (HT), Graves’ disease and autoimmune Addison’s disease (AD), as well as healthy controls. The frequency of CD20loCD27hiCD38hiHLA-DRint plasmablasts, CD86+CD14loCD16+ non-classical monocytes and two subsets of CD56dimHLA-DR+IFN-γ+ NK cells were increased in patients with HT. Subsets of CD56dimCD69+HLA-DR- NK cells and CD8+ TEMRA cells, both expressing IFN-γ, were expanded and reduced, respectively, in the N-T1D group. In addition, patients with AD were characterized by an increased percentage of central memory CD8+ T cells that expressed CCR4, GATA3 and IL-2. We demonstrate that patients with N-T1D, HT and AD had altered frequencies of distinct subsets within antigen-presenting and cytotoxic cell lineages. Previously unreported alterations of specific cell subsets were identified in samples from patients with HT and AD. Our study might contribute to a better understanding of shared and diverging immunological features between autoimmune endocrine diseases.